On sufficient conditions for the existence of bounded solutions of inhomogeneous linear extensions of dynamical systems - Grechko, A. L. (Ukrains’kyi Matematychnyi Zhurnal, 2010)
We study sufficient conditions for the existence of bounded solutions of linear extensions of the dynamical systems.